2003
DOI: 10.1046/j.1365-2761.2003.00493.x
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐based detection methods of Macrobrachium rosenbergii nodavirus, a pathogen of the giant freshwater prawn, Macrobrachium rosenbergii: dot‐blot, in situ hybridization and RT‐PCR

Abstract: The availability of specific and rapid detection methods is essential for monitoring the health status of farmed species, particularly in viral diseases as in this case early diagnosis is a critical factor in containing disease outbreaks. Three complementary genome-based methods were developed for the detection of Macrobrachium rosenbergii nodavirus (MrNV), i.e. dot-blot hybridization, in situ hybridization and reverse transcriptase-polymerase chain reaction (RT-PCR). Detection limits were established for dot-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
106
2
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(116 citation statements)
references
References 8 publications
6
106
2
2
Order By: Relevance
“…The protocol for the RT-PCR for detection of MrNV/XSV developed by Sri Widada et al [24] and Sahul Hameed et al [20,21] is recommended for all situations. MrNV and XSV can be detected by RT-PCR separately using a specific set of primers or these two viruses can be detected simultaneously using a single-tube one-step multiplex RT-PCR [32,36].…”
Section: Diagnostic Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The protocol for the RT-PCR for detection of MrNV/XSV developed by Sri Widada et al [24] and Sahul Hameed et al [20,21] is recommended for all situations. MrNV and XSV can be detected by RT-PCR separately using a specific set of primers or these two viruses can be detected simultaneously using a single-tube one-step multiplex RT-PCR [32,36].…”
Section: Diagnostic Methodsmentioning
confidence: 99%
“…Pathognomonic oval or irregular basophilic cytoplasmic inclusion bodies are demonstrated in the target tissues by histology [1,6]. The presence of MrNV in infected cells can be demonstrated in histological sections using a DIG-labelled DNA in situ hybridisation probe specific for MrNV [24].…”
Section: Clinical Signs and Histopathologymentioning
confidence: 99%
See 1 more Smart Citation
“…Several tests have been reported for detecting WTD which include dot-blot hybridization, in situ hybridization and reverse-transcriptase polymerase chain reaction (RT-PCR) [11], loop-mediated isothermal amplification (LAMP) [4], sandwich enzyme-linked immunosorbent assay (S-ELISA) [7] and triple antibody sandwich enzymelinked immunosorbent assay (TAS-ELISA) [6] for MrNV; dot-blot hybridization and RT-PCR for XSV [12] and onestep multiplex RT-PCR [13,16] for the detection of both MrNV and XSV. Sahul Hameed et al [9] reported western blot and ELISA for the detection of both MrNV and XSV.…”
mentioning
confidence: 99%
“…cDNA was synthesized from 1 lg of RNA using First Strand cDNA Synthesis Kit (Fermentas) with random hexamer primers. PCR was performed using specific primers (ATGGCTAGAGGTAA ACAAAATTC and ACAACCTAATTATTGCCGAC for MrNV [11] and CCACGTCTAGCTGCTGAC and CGGAA TAATGCCTAACCAAT for XSV [15]). The reaction mixture (25 lL) contained 12.5 lL PCR master mix (Fermentas), 25 pmol each of forward and reverse primers and 1 lL of cDNA.…”
mentioning
confidence: 99%